Conhecimento sobre HIV/Aids entre homens que fazem sexo com homens em 10 cidades brasileiras - Raquel Regina de Freitas Magalhaes Gomes (2014)
Introduction: An adequate HIV/AIDS knowledge is essential for the adoption of safe attitudes and practices and it is an important component for monitoring the epidemics in keypopulations most at risk of acquiring HIV infection. A low level of knowledge is detrimental to HIV prevention efforts and goes beyond individual characteristics. Studies among men who have sex with men (MSM) indicate low knowledge level and a lack of standardization of form and analysis of the data, and, in Brazil, there are few studies in this area. Objective: This study evaluated the level of HIV/AIDS knowledge among MSM in ten Brazilian cities, using the latent trait model estimated by Item Response Theory (IRT), and analyzed vulnerability, social, individual and programmatic factors associated with low knowledge on HIV/AIDS. Methods: A multicenter, cross-sectional study carried out between 2008 and 2009 in ten Brazilian cities. Adult MSM (n=3,746) were recruited through Respondent Driven Sampling (RDS). HIV/AIDS Knowledge was ascertained through ten statements obtained by face to face interview and latent scores were estimated by two-parameter logistic model (discrimination and difficulty) of TRI. Full information factor analysis was performed to test the unidimensionality of the knowledge scale. The differential item functioning (DIF) was used to examine groups of age and education. Ordinal logistic regression model was used to analyze vulnerability factors with low knowledge on HIV/AIDS and, for this analysis the knowledge scores were categorized as an ordinal variable in three ordered levels of knowledge: high, medium and low. Results: HIV/AIDS knowledge scores estimated by IRT did not exceed 6.0 (scale 0-10), with mean and median values of 5.0 (SD=0.9) and 5.3, respectively, with 40.7% of the sample with knowledge levels below the average. Some beliefs still exist in this population regarding the transmission of the virus by insect bites, by using public restrooms, and by sharing utensils during meals. With regard to the difficulty and discrimination parameters, eight items were located below the mean of the scale and were considered very easy, and four items presented very low discrimination parameter (< 0.34). The absence of difficult items contributed to the inaccuracy of the measurement of knowledge among those with median level and above. In the overall model, the following variables were independently associated with low knowledge: education 8 years, non-white skin color, Brazil criteria of economic class C, D-E, age <25 years old, age at the 1st intercourse 14 years old and not having been tested for HIV. Conclusion: The results indicated a worrying high proportion of participants with medium and low knowledge level, especially considering that the evaluated items are basic and well publicized information about the modes of HIV transmission. An adequate level of HIV/AIDS knowledge is fundamental to improving risk perception and motivation to adopt safe sex practices among MSM. IRT analysis, which focuses on the individual properties of each item, allows obtaining measures that do not depend on the set of items used, and provides better ascertainment and accuracy of knowledge scores. Valid and reliable scales are essential for monitoring HIV/AIDS knowledge in the MSM population over time and in different geographical regions, and the psychometric model IRT brings this advantage. Greater intervention the structural level is essential, where the factors of programmatic vulnerability have important elements to reduce individual and social vulnerability factors. We should mention the need to evaluate and develop new strategies to improve HIV/AIDS knowledge, particularly the most vulnerable segments of this population as young MSM with more unfavorable socioeconomic conditions, in order to increase their awareness of HIV prevention and care.